PUBLIC COMPLAINT SERVICE QUALITY FOR POLRI MEMBERS AT LAMPUNG REGIONAL POLICE - Oktavian Laido; Malik (International Journal of Multidisciplinary Reseach, 2026)
This study uses a descriptive qualitative research design to describe and analyze the quality of public complaint services concerning Indonesian National Police (Polri) personnel at the Lampung Regional Police. Data were collected directly from field informants through interviews and document study. The findings show that: (1) in the tangibles dimension, complaint-service facilities are available, but supporting facilities and infrastructure remain limited; (2) in the reliability dimension, services are implemented according to procedures, although delays still occur in complaint handling and information delivery; (3) in the responsiveness dimension, service officers are fairly responsive, but the speed of follow-up on reports still needs improvement; (4) in the assurance dimension, officers have attempted to provide security and certainty to the public, yet some community members remain uncertain about complaint resolution; and (5) in the empathy dimension, officers demonstrate friendly and polite attitudes, but attention and communication need to be strengthened so that complainants feel more comfortable and respected throughout the complaint-service process.